Peranan Ekonomi Syariah Dalam Perkembangan Digitalisasi Ekonomi Terkait Prospek Marketplace Di Indonesia - Ilyas Nurul Azam (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Disruption also turns trade transactions commonly done in physical markets into virtual markets, or commonly referred to as marketplaces. The change turned out to bring many opportunities so that not a few businesses start even switching their business to the online world. In addition to creating opportunities for businesses, the change is also enjoyed by consumers who want to buy products or services because cenderueng facilitate transactions ithout having to meet physically. However, some of these economic actors take advantage of these changes regardless of the limits of sharia. Sharia economic values that are collected universally, in the form of monotheism (faith), 'adl (justice), nubuwwah (prophecy), khilafah (leadership), and ma'ad (results). From these values, it is then stated in the goals of Islam, namely maqoshid syari'ah which is composed of religion (hifdz ad-din), soul (hifdz an nafs), reason (hifdz al-aql), honor (hifdz an-nasl), and wealth ( hifdz al maal) which will describe the role of the Islamic economy in digitalizing the economy,especially in the marketplace. In writing this thesis, the writer uses research qualitative, namely research that intends to understand the phenomenon about what is experienced by research subjects such as behavior, perceptions, motivations, actions and others holistically and in a way description in the form of words and language, in a special natural context and by utilizing various scientific methods.From this research, it is intended that Sharia economy has a role to play in the development of economic digitalization, especially in the prospect of marketplace in Indonesia. In this case, the authors used qualitative research methods with a type of library research (literature) and produce relevant points of the role of Sharia economy in the development of economic digitization related to the prospects of marketplaces in Indonesia.